2022
DOI: 10.1177/03635465221096464
|View full text |Cite
|
Sign up to set email alerts
|

The Control of Anteromedial Rotatory Instability Is Improved With Combined Flat sMCL and Anteromedial Reconstruction

Abstract: Background: Both the superficial medial collateral ligament (sMCL) and the deep MCL (dMCL) contribute to the restraint of anteromedial (AM) rotatory instability (AMRI). Previous studies have not investigated how MCL reconstructions control AMRI. Purpose/Hypothesis: The purpose was to establish the optimal medial reconstruction for restoring normal knee kinematics in an sMCL- and dMCL-deficient knee. It was hypothesized that AMRI would be better controlled with the addition of an anatomically shaped (flat) sMCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 41 publications
3
36
0
3
Order By: Relevance
“…When combined with an sMCL limb, stability was restored to the intact state. This was followed by Behrendt et al, 5 who tested 5 different constructs. They determined that it was possible to restore stability when an anteromedial reconstruction, placed in similar position to the dMCLR used in Miyaji et al 26 and the present study, was combined with a flat sMCL limb.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When combined with an sMCL limb, stability was restored to the intact state. This was followed by Behrendt et al, 5 who tested 5 different constructs. They determined that it was possible to restore stability when an anteromedial reconstruction, placed in similar position to the dMCLR used in Miyaji et al 26 and the present study, was combined with a flat sMCL limb.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of attention to rotatory stability is reflected in the multitude of surgical reconstruction techniques that have been developed to restore valgus stability, 10,18,21,24,46 usually with a superficial medial collateral ligament (sMCL) limb, while only recently have reconstructions included a deep MCL (dMCL) limb to restore rotatory stability. 5,20,26,40 While the MCL is the most injured ligament of the knee, surgical techniques for its repair and reconstruction have received less attention than the cruciate ligaments and the posterolateral corner, likely as a result of its excellent healing potential in the isolated setting. 8,12,13,25,29,31,38 This has begun to change, as multiple recent studies have highlighted the increased anterior cruciate ligament (ACL) rerupture rate if medial-sided instability is not addressed at the time of ACL reconstruction (ACLR), likely due to increased forces on the ACL graft.…”
Section: -In-5mentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior of the different fiber bundles of the sMCL suggests that a single-strand reconstruction cannot imitate the broader, flatter native ligament. Indeed, Behrendt et al 4 have shown that a flat sMCL reconstruction was more effective in restraining valgus tibial rotation and ER. However, only the addition of an anteromedial reconstruction fully restored medial knee kinematics in an sMCL/dMCL-deficient knee.…”
Section: Discussionmentioning
confidence: 99%
“…For isolated dMCL reconstruction associated with an ACLR, a gracilis can be used percutaneously to reconstruct the dMCL. 3 For dMCL + sMCL reconstruction, an anteromedial reconstruction using gracilis can be performed to control external rotation and can be combined with a flat sMCL reconstruction 2 to biomechanically best restore medial knee stability. In all MCL surgeries, the position of femoral insertion of the graft is critical.…”
Section: Video Transcriptmentioning
confidence: 99%